Consumer Acceptance for Vegetable Pigeonpea through front line Demonstrations in Central Gujarat - A. K. Rai , S. Khajuria , Kanak Lata , J. K. Jadav , Rajkumar and B. S. Khadda, (Indian Journal of Extension Education, 2017)
Conventional pigeonpea (Cajanus cajan (L.) Millsp.) is harvested as seed but for the purpose of vegetable, it is harvestedas pods when it is immature. At two stages it is a nutritious and delicious vegetable and forms a substitute for green pea(Pisum sativum (L.). Pigeonpea is one of the most important pulse crops of the Panchmahals district of Gujarat. However,productivity of pigeonpea in the district is very low. Attempts are made to improve productivity and to increase area underpigeonpea by adopting HYVs (High Yielding Variety). In order to compare and contrast conventional pigeonpea withHYVs varieties, 75 frontline demonstrations were carried out in a systematic manner on farmers' field to show the worthof new varieties in comparison to local check and thereby convincing farmers about potentialities of improved productionmanagement practices of pigeonpea for further adoption, involving feasible and effective scientific package of practices.The demonstrations clearly showed enhancement of productivity, at the same time area under pigeonpea cultivation wasalso noticed to be enhanced. The yield (green pod) was found to increase from 4300 kg/ha in local check to 7300 kg/ha indemonstrations. Similarly, the benefit cost ratio for HYVs varieties was found to increase to 3.22 as compared to localcheck (2.27). The economics and benefit cost ratio can be further improved to 3.23 by giving slightly higher inputs forcultivation and marketing. The impact of FLDs was analyzed which showed improvement of knowledge and satisfactionof farmers as the main reason for mass scale adoption.